(untitled) (Indian Journal of Child Health, 2021)
Background: Cardiovascular diseases (CVDs) are the leading cause of mortality throughout the world. Breastfeeding has been shown to play a role in the prevention of CVD. The International Code for Marketing of Breastmilk Substitutes (BMSs) and its relevant resolutions (the Code) were adopted by the World Health Assembly to protect breastfeeding. Aim: This study aims to study the relationships between breastfeeding rates and laws that cover the code with CVD risk factors (obesity and blood pressure) and death from non-communicable diseases (NCDs). Methods: Data for scores given to national laws and provisions under the Code for protecting breastfeeding were obtained from the World Health Organization (WHO)/International Baby Food Action Network report in 2020. Data for exclusive breastfeeding (EBF) during infancy were obtained from United Nations International Children’s Emergency Fund Global data. The WHO data for CVD risk factors in adults (>18 years) included overweight, obesity raised blood pressure (RBP), raised blood glucose level (RBGL), and death from NCDs. Results: There were significant negative correlations of overweight, obesity, raised BP, and death from NCD with EBF and with scores given to national laws that cover the Code. RBGL correlated negatively with overweight and obesity. Overweight, obesity, RBP, and death from NCDs correlated inversely with provisions in the national laws for monitoring and enforcement at p<0.015. Engagement of health staff and systems and promotion in health facilities correlated with RBP and death from NCDs at p<0.01. Conclusions: Prevention of CVD can benefit from improving breastfeeding rates by the enactment of national laws that cover the Code in its entirety. All countries should enact, monitor, and enforce these laws for promoting and protecting breastfeeding and preventing long-term consequences of feeding BMS.